DESKRIPSI PEMAHAMAN KONSEP MATERI DAN PERUBAHANNYA SISWA KELAS X SMK SMTI PONTIANAK - Nurhafizah, Nurhafizah; Melati, Husna Amalya; Rasmawan, Rahmat (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstrakThe purpose of this research was to describe the students understanding concept in matter and its changes in grade Xth of SMK SMTI Pontianak. A descriptive method was employed in this study. As many as 24 students participated as the subject. Essay test and interviews guidelines were used to collect data. According to data analysis show the percentage of student’s conceptual understanding in concept; (1) deinition of matter was 4% (2) grouping of matter was 89.3% (3) solid was 58.3% (4) liquid was 61.1% (5) gas was 40.3% (6) element was 79.2% (7) compound was 54.2% (8) mixture was 29.2% (9) particle of matter was 29.2% (10) metal element was 87.5% (11) nonmetal element was 87.5% (12) homogeneous was 83.3% (13) heterogeneous was 86.1% (14) distillation was 41.7% (15) filtration was 58.3% (16) sublimation was 16.7% (17) recrystallization was 8.3% (18) chemical change was 80.8% (19) physic change was 68.7%. The average of student’s conceptual understanding was 55.9% which caregorized as enough..Keywords: conceptual understanding, matter, material changes